Aborsi Ditinjau Dari Segi Medis - Cholifatun, Siti (Musawa Jurnal Studi Gender dan Islam, 2003)
Abortion is one of the oldest methods of family planning in the world. Yet apart from it still being controversial from a moral-ethical perspective except in emergency situations, the abortion of a fetus can also be dangerous from a health perspective. If it is not done properly and correctly by professionals, abortion can lead to the patient experiencing complications such as bleeding, infection of the reproductive organs, infertility and even death. This article stresses that complications such as these can only be avoided if abortions are carried out professionally by experts.